ETIKA KERJA PEGAWAI DALAM PELAYANAN KONSUMEN DI PDAM TIRTA KHATULISTIWA KOTA PONTIANAK - Ridho Fiardhi E.21109056 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This paper is motivated by the phenomenon of low levels of employee adherence to the operating instructions, the service does not follow a predetermined procedural and not disciplined in working hours. Based on these phenomena formulation of the problem of this paper is the work ethic of employees in customer service in PDAM Tirta Equatorial Pontianak with aspects of professionalism, transparency, and responsibilities of employees in service delivery. Service professionalism is seen by the rapid service delivery and on time does not meet consumer expectations. Follow-up of complaints customers have not been followed by the honesty of employees because the field reveal any unofficial payments. Transparency in service delivery has not been implemented as required konsumen.Tanggung discipline responsible employees in terms of work in general is low it is still seen by disciplinary violations committed by employees. Keywords: Service professionalism, service charge transparency, responsibility towards work.